An integrative literature review on clinical decision-making of novice nurses for disaster management in the Emergency Room - Rystika Angga Sari; Retno Lestari; Yati Sri Hayati (PAGEPress Publications, 2024)
Novice nurses play a workflow part in responsibility among an overwhelming of patient. This emphasizes the need for nurses to have comprehensive decision-making skills, especially in disaster management. However, in practice, clinical decision-making remains a challenging issue for novice nurses working in the Emergency Room (ER). This review was conducted to synthesize the strategy that novice nurses need to do in clinical decision-making in the ER during a disaster. This review used an integrative literature review approach to identify (n=16) relevant scientific articles. Six online databases (ScienceDirect, Proquest, Sage Journals, PubMed, Willey Library, and EBSCO) were utilized to identify articles published between 2013 and 2023. The gathered articles were selected using the PRISMA method by removing duplicate articles and those that did not align with the review's objectives. The PRISMA flowchart was used to illustrate the evidence search process. Out of a total of 2,264 identified articles, sixteen articles are relevant for review. The review revealed that clinical decision-making requires careful consideration in several aspects which focused on determining the priorities of triage, assessment, diagnostic skills, and communication skills in teamwork during a disaster in the ER. This review provides evidence that the accuracy of clinical decision-making is a major influence on patient outcomes during disaster management. In conclusion, comprehensive training and more education for novice nurses about disaster precision nursing in the future are needed to reduce errors in decision-making.